Effects of oil characteristics on the performance of shoreline response operations: A review - Chen, Xinya; Bi, Huifang; Yue, Rengyu; Chen, Zhikun; An, Chunjiang (Frontiers in Environmental Science, 2022)
Marine oil spills are serious ecological disasters that have massive adverse impacts on the environment. The impacts are even worse once the spilled oil is stranded on a shoreline. A series of shoreline cleanup methods are deployed to remove spilled oil, but their performance can be affected by the stranded oil. This review therefore comprehensively investigates the characteristics of spilled oil on the shoreline and explores their effects on the effectiveness of shoreline response operations. First, the five basic groups of spilled oil (i.e., non-persistent light oils, persistent light oils, medium oils, heavy oils, and sinking oils) are discussed and each oil fraction is introduced. Three distribution scenarios of adhered oil on shorelines are also analyzed. The effects of oil characteristics, such as oil type, viscosity, evaporation, and composition, on the performance of chemical treatments, physical methods, and biodegradation are then discussed and analyzed. Finally, the article provides recommendations for future research on aspects of shoreline oiling prevention, quick responses, response tool sets, and other considerations, which may have significant implications for future decision-making and the implementation of shoreline cleanups to effectively remove stranded oil.